UJI DAYA HAMBAT EKSTRAK KULIT LIDAH BUAYA (ALOE BARBADENSIS MILLER) TERHADAP BAKTERI E. COLI - DIAN ANNISA RAHIM; CUT MOURISA (JURNAL ILMIAH MAKSITEK, 2020)
Escherichia coli (E. coli) is a gram negative bacteria that has a short stem (cocobacil) form and is a bacteria that have a highlevel of resistance. E. coli can cause various infectious diseases in some systems. Aloe vera skin is a plant which containsanthraquinones, tanins, saponins, and flavonoids. This substance has effect as an antibiotic and antiseptic. This study aimsto compare the sensitivity of aloe vera extract with cotrimoxazole in E. coli growth. This study used an experimental method.The technique used to measure antibiotic activity is the method of disk diffusion. Aloe vera skin (Aloe barbadensis Miller) atconcentrations of 25%, 50%, 100%, kotrimoksazol, and aquadest resulted in average diameter of clear zone. Aloe vera skin(Aloe barbadensis Miller) have an inhibitory power against E.coli.